SOCIAL DIMENSION OF COLLECTIVE MEMORY - Mozghova, Natalia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The rapid changes taking place in the age of globalization are modifying the attitudes toward time and disrupting its linear vision. Nowadays the absolute uncertainty looms over the image of the future. Mentioned above necessarily brings us to the problem of identity, which primarily concerns memory. After all, it is memory (individual, collective) that makes us who we are, shaping our identity and determining our belonging to a certain community. The aim and tasks of the research is to theoretically reconstruct speculative searches of the foundations of the phenomenon of collective memory. Research methods are to analyze the modern literature devoted to studying of phenomenon of a collective memory; to compare traditional and postmodern paradigms in understanding the essence of the phenomenon of a collective memory; to identify further prospects for the transformation of collective memory in a situation of postmodern disintegration. Research results. The interdisciplinary method was used to consider the phenomenon of collective memory in cultural anthropology, sociology, psychology, political science, philosophy; method of historiographical analysis – for the systematization of primary sources and scientific literature, devoted to studying the phenomenon of collective memory; hermeneutic method – for explanation and interpretation of works of contemporary authors who are specialists in this field of scientific knowledge today; comparative analysis – to compare traditional and postmodern understanding of the essence of collective memory. No less fruitful there was the method of categorical-conceptual analysis, which made it possible to specify and clarify the terminological chaos that prevails today in the scientific works of native and foreign scientists. Along with the above, such general scientific methods as comparison, analysis and synthesis, induction and deduction, abstraction and concretization, etc., have played an important role. Discussion At all times, at the individual memory level people have used a two-part temporal division (present and non-present, or past and non-past) instead of a three-part temporal division (past – present – future). Thus, two different concepts of time concern the difference of the subjective and social (linear, quantitative, irreversible) time, differences of cultures with different experience of perceiving time Conclusion. Summarizing we state that the term "collective memory" should be used referring to memories that have been gained in direct experience and reflected the value system most relevant to a particular community. Collective memory is an integral part of public consciousness, which can determine the direction of social action in the absence of a well-developed policy of memory.